Rational Design of Pepsin for Enhanced Thermostability via Exploiting the Guide of Structural Weakness on Stability - Zhao, Yue; Miao, Yulu; Zhi, Fengdong; Pan, Yue; Zhang, Jianguo; Yang, Xuepeng; Zhang, John Z. H.; Zhang, Lujia (Frontiers in Physics, 2021)
Thermostability is considered to be an important parameter for measuring the industrial value of enzymes; however, most of natural enzymes are incapable of meeting industrial thermostability requirements. Currently, there is numerous thermostability prediction software, but they possess poor applicability as they cannot be aimed at structural weaknesses. Aspartic proteases are widely used in industrial processing; however, their thermostability is insufficient for large-scale production requirements. In this study, we explored a combination of structural characteristics and prediction software for thermostability modification by improving the thermostability of a typical aspartic protease-pepsin. Based on the structural characteristics of pepsin and the experimental results of mutations provided by several energy-based prediction software, it was found that the main structural weakness of pepsin is the flexible regions on the surface. Based on this weakness and computational design, several mutations were identified. The half-lives of mutant D52N and S129A at 70 °C increased by 200.0% and 66.3%, respectively. Our research showed that protein structural weakness can assist thermostability modification, and combined with computational design, can increase design efficiency and accuracy.